Exploring English Teacher Experience Using Differentiated Instruction in Teaching English - Moh Rofiki; Sujito (Indo-MathEdu Intellectuals Journal, 2026)
Differentiated learning is an important approach to addressing the diversity of students' learning needs in English language learning. This study aims to explore teachers' experiences in implementing differentiated learning and identify various challenges faced during the implementation process. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews and classroom observations of English teachers implementing differentiated learning. Data were then analyzed using descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that teachers implement differentiated learning through three main stages: planning, implementation, and assessment, which are manifested in the differentiation of content, process, and product according to students' needs, interests, and learning readiness. The research findings reveal that the successful implementation of differentiated learning is largely determined by teachers' ability to map student characteristics and adapt learning strategies flexibly. However, teachers still face various obstacles, such as limited time, lack of learning resources, high variation in student abilities, and limited competency in designing differentiated learning. These findings imply the need for ongoing training and institutional support to improve the effectiveness of the implementation of differentiated learning in schools.